ANALISIS KEUNTUNGAN DAN STRATEGI PENGEMBANGAN USAHA LOBSTER (Panulirus spp. ) PADA CV. SEA QUEEN KOTA KENDARI - Soelaiman Hardi; Budiyanto Budiyanto; Roslindah Daeng Siang (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2017)
This study aims to determine the cost structure, income level and trade development strategy on marine lobster in CV.Sea Queen City of Kendari. The research location determined by purposive. Data were collected by interview, observation and documentation, which are sourced from business owners (1) and employees (6). The results showed that the cost structure of the business consists of investment operations of Rp1,357,721,000, a fixed fee of Rp192,406,548/year and variable costs of Rp1,637,932,600/year, bringing the total cost of Rp1,830,339,148/year, Gross revenue of Rp2,100,000,000/year and net income Rp269,660,852/year. In the company's business development strategy there are 8 of harnessing the rapid technological, increase business capital, increase product capacity, improve the promotion, recruitment, increase production volumes lobster, pursuing a strategy of stocks of raw materials, and improve the whole lobster resources owned businesses.